DisELExia-GPT: Inteligencia Artificial Generativa para el Aprendizaje Inclusivo y Personalizado del Español en Entornos Digitales - Clementi, Luca; Jiménez López, María Dolores (Diálogos Latinoamericanos, 2025)
The integration of Generative Artificial Intelligence (GenAI) in digital and distance education is reshaping language teaching. This article presents DisELExia-GPT, a GPT-4o-based system tailored to support students with dyslexia and other Specific Learning Disorders (SLDs) in learning Spanish. DisELExia-GPT combines advanced technologies such as DALL-E-generated visual translations, image recognition, and adaptive tests in grammar, vocabulary, and comprehension, all with instant feedback. It also includes speech recognition and synthesis tools to foster accessibility and inclusion in learning. The system exemplifies how GenAI can personalize education, adapting content to learners’ proficiency levels and specific needs. Grounded in principles of adaptive learning and educational inclusion, DisELExia-GPT stands out as an innovative tool that enhances virtual language instruction. The study underscores its role as an intelligent language assistant and its transformative potential in inclusive digital education.